The Secrets of the FBI - Kessler, Ronald (New York Broadway Paperbacks, 2012)
Draws on agent interviews about famous FBI cases to reveal the Bureau's inner workings and some of its most deeply held secrets.
Include Index and Illustration
Keywords: Official secrets -- United States -- United States. Federal Bureau of Investigation